Pengaruh Kepemimpinan, Kompetensi, dan Disiplin Terhadap Kinerja dengan Motivasi Sebagai Variabel Mediasi Pada Guru SMP Kabupaten Tambrauw - Nauw, Karel; Ismail, Tubagus; Purwanto, Agus Joko (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of principal leadership, teacher competence, and work discipline on teacher performance with work motivation as a mediating variable. The method used is quantitative with SEM-PLS analysis techniques. The population consists of 136 teachers, with a sample of 85 teachers. The results of the study indicate that teacher competence has a significant effect on teacher performance, while principal leadership, work discipline, and work motivation are not significant. Work motivation is also not proven to be a mediator. The implication is that it is recommended to focus on improving teacher competence.